The Influence of Teacher’s Supervision and Professionalism on Teacher’s Performance - Yusuf, Muhammad; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2020)
This study determined the effect of supervision and professionalism on teacher performance in State Junior High Schools of SP. Padang. This research uses quantitative methods. The population in this study were all junior high school teachers with the status of Civil Servants in SP. Padang. While the sample was obtained by totaling sampling technique with 51 respondents. Data collected by documentation, questionnaires, and observations. Data analysis techniques using simple linear regression formula and multiple linear regression with the help of SPSS software. The results of the study concluded that there was an influence of supervision and on the teacher performance of the State Junior High Schools of SP. Padang. There is an influence of teacher professionalism on teacher performance in State Junior High Schools of SP. Padang. There is an influence of teacher supervision and professionalism together on the teacher performance of State Junior High Schools of SP. Padang.